Formulation of facial liquid soap wıth 4-(Dimethylamino) chalcone and virgin coconut oil as antibacterial agents against acne-causing bacteria - Putri Wulandari; Esti Mumpuni; Esti Mulatsari; Kartiningsih Kartiningsih (Faculty of Pharmacy, Universitas Pancasila, 2025)
Acne vulgaris is a multifactorial skin disorder commonly associated with infections caused by Staphylococcus epidermidis and Cutibacterium acnes. This study aimed to develop and evaluate an antibacterial facial liquid soap containing 4-(Dimethylamino) chalcone and virgin coconut oil (VCO). The synthesized chalcone, a flavonoid derivative obtained through the Claisen–Schmidt condensation reaction, was characterized using TLC, melting point analysis, UV-Vis spectrophotometry, and LC-MS/MS. Formulations containing 1.25% and 2.5% chalcone combined with 40% VCO were prepared and tested. Antibacterial activity was evaluated using the agar diffusion method, while physical properties were assessed through organoleptic observation, homogeneity, foaming ability, pH measurement, stability testing, and skin irritation tests. The 1.25% chalcone formulation demonstrated strong antibacterial activity, producing inhibition zones of 19.40±0.39 mm against C. acnes and 18.97±0.45 mm against S. epidermidis. All formulations were stable, homogeneous, and non-irritating. These findings indicate a synergistic antibacterial effect between chalcone and VCO, supporting their potential use as natural active ingredients in anti-acne facial soap formulations.